2021
DOI: 10.3390/jof7070497
|View full text |Cite|
|
Sign up to set email alerts
|

Freeing Aspergillus fumigatus of Polymycovirus Infection Renders It More Resistant to Competition with Pseudomonas aeruginosa Due to Altered Iron-Acquiring Tactics

Abstract: A virus-free (VF) A. fumigatus isolate has been shown to be resistant in competition with Pseudomonas as compared to the isogenic line infected with Aspergillus fumigatus polymycovirus 1 (AfuPmV-1), and this phenotype was apparently related to alterations in iron metabolism. Here we investigated further the mechanisms underpinning this phenotype. The extracellular siderophore profiles of five isogenic VF and virus-infected (VI) strains were sampled at 24, 31, 48, 54, and 72 h in submerged cultures and quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 26 publications
2
22
1
Order By: Relevance
“…Infection has also been reported to increase sensitivity to antifungals [3] and to the bacterium Pseudomonas aeruginosa [6]. Although the molecular mechanisms underpinning the above phenotypes have not been elucidated, there is evidence that polymycoviruses modulate host carbon, nitrogen and iron metabolism [5, 7]. Finally, polymycoviruses are targeted by the host RNA silencing machinery [8].…”
Section: Pathogenicitymentioning
confidence: 99%
“…Infection has also been reported to increase sensitivity to antifungals [3] and to the bacterium Pseudomonas aeruginosa [6]. Although the molecular mechanisms underpinning the above phenotypes have not been elucidated, there is evidence that polymycoviruses modulate host carbon, nitrogen and iron metabolism [5, 7]. Finally, polymycoviruses are targeted by the host RNA silencing machinery [8].…”
Section: Pathogenicitymentioning
confidence: 99%
“…Polymycovirus infections are associated with various alterations in hosts, including changes in pigmentation, sectoring, and decreased host growth and host virulence, as well as increased sporulation, host growth, host virulence, and improved sensitivity to antifungals ( Kanhayuwa et al, 2015 ; Zhai et al, 2016 ; Kotta-Loizou and Coutts, 2017 ; Niu et al, 2018 ; Takahashi-Nakaguchi et al, 2020 ; Filippou et al, 2021 ; Patil et al, 2021 ). In this study, we therefore compared the colony morphology, growth rate, and biomass production of the virus-infected strain LSH3 with those of the virus-cured strain LSH3VF.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of mRNA expression patterns at the transcriptome level following infection with polymycoviruses in fungi is vital for understanding the mechanism underlying mycovirus-mediated alterations in pathogenic fungi. Previous studies have demonstrated that polymycovirus infections alter the phenotypes of virus-infected and isogenic virus-free strains ( Kanhayuwa et al, 2015 ; Zhai et al, 2016 ; Kotta-Loizou and Coutts, 2017 ; Niu et al, 2018 ; Takahashi-Nakaguchi et al, 2020 ; Filippou et al, 2021 ; Patil et al, 2021 ). However, there are no reports on the alterations in transcript accumulation in polymycovirus-infected fungi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Siderophore mobilization was slowed in virus-infected strains, and the consequent drop in Aspergillus fitness impaired its competition for iron with P. aeruginosa . In contrast, due to shifts in iron-acquiring tactics, the reservoir of the siderophore TAFC was consumed more rapidly by the virus-free A. fumigatus strain, which better withstood competition for iron with P. aeruginosa [60]. Third, both small and large molecular weight mammalian siderophores representatives warrant attention due to their involvement in iron scavenging.…”
Section: Role Of Siderophores As Diagnostic Target In Various Patient...mentioning
confidence: 99%